Buoyancy of convective vertical motions in the inner core of intense hurricanes - Eastin, Matthew D., author; Gray, William M., advisor; Schubert, Wayne, H., committee member; Montgomery, Michael T., committee member; Bienkiewicz, Bogusz, committee member; Black, Peter G., committee member (Colorado State University. Libraries, 2003)
The buoyancy of hurricane inner-core convective vertical motions is studied using extensive aircraft data from 175 radial legs collected in 14 intense hurricanes at four altitudes ranging from 1.5 to 5.5 km. Vertical motion events, called cores, are identified using the criteria that the convective-scale vertical velocity must exceed an absolute value of 1.0 m s–1 for at least 0.5 km. A total of 620 updraft cores and 570 downdraft cores are included in the dataset. Core properties are summarized for the eyewall and rainband regions at each altitude. Populations of core convective vertical velocity and diameter are approximately lognormally distributed. Roughly 70% of cores are superimposed upon mesoscale ascent. Eyewall cores are stronger and wider than rainband cores. Updraft cores in both regions exhibit a slight increase in strength and size with altitude. Downdraft cores tend to be weaker and narrower than updraft cores with less vertical variation. Over 54% of eyewall updraft cores and 63% of rainband updraft cores exhibit positive total buoyancy. Updraft cores with positive total buoyancy occupy less than 5% of the total eyewall and rainband areas, but accomplish ~40% of the total upward mass, heat, and moisture transport. A one-dimensional updraft model is used to elucidate the relative roles played by buoyancy, water loading, vertical perturbation pressure gradient forces, and entrainment in the vertical acceleration of "typical" updraft cores. The (positive) median total buoyancy values are found to be more than adequate to explain the vertical accelerations in observed median updraft core strength, which implies that typical vertical perturbation pressure gradient forces are directed downward and largely oppose the positive buoyancy forces. Entrainment and water-loading are also found to limit updraft magnitudes. Three cases are examined in greater detail. In each, mid-level vertical velocity and radar reflectivity are asymmetric and exhibit a persistent relationship with the direction of the large-scale vertical wind shear. The mesoscale vertical velocities are dominated by a quasi-stationary wavenumber-one asymmetry with maximum ascent downshear left and weaker descent upshear. Mesoscale reflectivity maxima are located left of the shear, and downwind of the mesoscale ascent maxima. Over 70% of buoyant updraft cores and short-lived convective-scale reflectivity cells are located downshear. Over 60% of convective downdraft cores that transport significant mass downward are located upshear with negative buoyancy dominant in upshear-left cores and positive buoyancy dominant in upshear-right cores. For two cases, buoyant updraft cores encountered in the mid-level eyewall exhibit equivalent potential temperatures (Θe) much higher than the Θe observed in the low-level eyewall, but equivalent to the Θe found in the low-level eye. Asymmetric low-wavenumber circulations appear responsible for exporting the high-Θe eye air into the relatively low-Θe eyewall and generating the locally buoyant updraft cores. Implications of these results upon conceptual models of hurricane structure and evolution are discussed. Three mechanism are suggested whereby asymmetric buoyant convection could significantly contribute to hurricane evolution.
Keywords: atmosphere